D-SALMA'S CATALOG SMART EFFECTIVELY INCREASES KNOWLEDGE OF PREGNANT WOMEN IN PREVENTING DENTAL CARIES - Salmawati Salmawati; Soeharyo Hadisaputro; Lanny Sunarjo; Bambang Sutomo (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: Pregnant women are one of the vulnerable groups to dental caries with a prevalence of 84.7%. During pregnancy, hormonal changes occur characterized by nausea, vomiting and laziness to brush teeth, acidic nature and changes in salivary pH cause dental caries. This condition can result in babies born with low body weight (BBLR), miscarriage, and pre-eclampsia. One of the efforts to increase knowledge in the maintenance of dental and oral health for pregnant women is to do promotion and prevention with educational media D-Salma's Catalog Smart, which is the development of a model of the caries catalog, this media is a picture book equipped with a pen book and in a special design using sensors to facilitate the pen book read and explain the content of the material. Objective: Produce a decent educational model and analyze theeffectiveness of v ity to increase the knowledge of pregnant women in preventing dental caries. Method: Type of R&D research, methode Quasy experiment Pre-Posttest group design (nonequevalent control group design). In the application of the model using a sample of 60 pregnant women divided into 2 intervention groups with the D-Salma's Catalog Smart model and a control group with a booklet. The variables measured are knowledge and OHIS of pregnant women. Data analysis used univariate analysis, bivariate analysis (Paired Sample T-test and Independent Sample T-test) and multivariate analysis with (linear regression). Results: Model D-Salma's Catalog Smart is validated and feasible to be applied as a medium for dental health education. The results of the effectiveness test increased knowledge from 3.40 to 8.00 (p = 0.000), and decreased the OHIS score from 3.90 to 1.00 (p = 0.000). Conclusion: The application of D-Salma's catalog smart model is feasible and effective in increasing the knowledge of pregnant women in preventing dental caries.